Сутність системи управління розвитком промислового підприємства - Харченко, В.А. (Економіка промисловості, 2013)
Розкрито сутність економічної категорії «система управління розвитком промислового підприємства» як системи, що об’єднує фінансово-економічні та виробничо-технічні управлінські рішення щодо досягнення цілей розвитку підприємства і регулює зв’язки між складовими частинами даної системи на основі оптимізаційних заходів, що дозволяє визначити пріоритети та узгодити цілі розвитку. Раскрыта сущность экономической категории «система управления развитием промышленного предприятия» как системы, объединяющей финансово-экономические и производственно-технические управленческие решения по достижению целей развития предприятия и регулирующей связи между составными частями данной системы на основе оптимизационных мероприятий, что позволяет определить приоритеты и согласовать цели развития. The aim of the article is to develop the theory of the notion ‘management system of industrial enterprise development’ under the existing economic circumstances. In order to achieve this the following terms have been studied: the ‘system’ from the systems theory, ‘management’ and ‘development’ from the management theory, ‘system management’ from the system analysis, as well as the ‘system approach’ and ‘management system’. The characteristics of these economic notions have been generalized and there have been defined those that allow one to form the content of the examined complex economic category ‘management system of industrial enterprise development’. This one, in its turn, according to the author, is a system uniting the processes of development and realization of financial-economic and production-technical decisions aimed at the development of an economic enterprise and regulating the interconnections between the integral parts of this system on the basis of optimization processes to achieve and ensure the efficiency of functioning in the existing economic conditions. Unlike the existing approaches, which expand on the interconnection between the subject and the object of management, the present definition underlines the necessity: to define the interconnections between the integral parts of the system, and take these into account during the development and realization of managerial decisions; to determine the influence of management subsystems during their interaction on the enterprise’s functional efficiency; to eliminate the disagreements between the tasks that are solved during the management of integral parts of the management system on the basis of prioritizing and coordination of tasks and aims of economic entities. There has been suggested to consider the management system of industrial enterprise development as a complex of subsystems of internal and external conditions. The subsystems of internal condition are the ones of production and marketing of products, financial and resource condition, which include elements of management. The subsystem of external condition includes economic, political, market and social factors (elements). The control of a complex of elements, which form the development management system, eliminates the disagreement between their management tasks and facilitates the achievement of the aims of industrial enterprises development.